Hubungan Kekuatan Otot Tungkai terhadap Kemampuan Menggiring Bola dalam Permainan Futsal Club Futsal SDN 78 Nagauleng - Hidayat, Fadly; Andi Mutmainna; Andi Ogo Darminto (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the relationship between leg muscle strength and the ability to dribble when playing football. The research used was quantitative research using a correlation test involving 15 students. Data collection techniques were carried out using instruments for assessing dribbling ability and leg muscle strength (skipping), for data analysis techniques using descriptive analysis and inferential analysis using the SPSS application. The results of the analysis showed that leg muscle strength obtained a significance level value of (0.039 < 0.05) while ball dribbling ability obtained a significant value of 0.039, where the probability value was smaller than the significance level value, namely 0.05 or (0.039 < 0.05). It can be stated that leg muscle strength has a relationship with the ability to dribble the ball. To test the interpretation of the correlation coefficient according to the level of relationship, it was found that both relationships were negative with a value of -536 in the interval 0.40 – 0.59. So, based on the person's level of interpretation of the coefficient, it is stated that the level of relationship between the research variables is in the medium category